If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 3(x + -4) + 6 = 0 Reorder the terms: 18 + 3(-4 + x) + 6 = 0 18 + (-4 * 3 + x * 3) + 6 = 0 18 + (-12 + 3x) + 6 = 0 Reorder the terms: 18 + -12 + 6 + 3x = 0 Combine like terms: 18 + -12 = 6 6 + 6 + 3x = 0 Combine like terms: 6 + 6 = 12 12 + 3x = 0 Solving 12 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 0 + -12 3x = 0 + -12 Combine like terms: 0 + -12 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| Y-(-2)=6/1(x-2) | | 10+12=14y-1-13y | | 3.25g+1.25g=81 | | 15X+4=10X+21 | | ay=5y+16 | | 12d=11 | | 15-3(x+5)-2= | | c-13=-1 | | 4(3p+2)-5(6p-1)=2(p-8)-6(7p-4) | | 6+4(x-1)+8= | | -12+8+(-2)= | | 5(x+4)-10= | | -2x-5=-2+1 | | 16p+14q= | | https://media.education2020.com/evresources/3108-05-05/mc018-1.jpg | | 3(x-1)+7= | | 9x-27=6x+12 | | -3+11=10y-13-19y | | (6x+2)-16=0 | | 8c-4/6c-3 | | 9x^2-24x-65=0 | | -7/3×n=-42 | | logx=2.45 | | -42-32r= | | 23+21z= | | B*8=96 | | -11v= | | 48=8-10n | | s^2+15s+20=0 | | 10x+5x-3x=120 | | 1+20xX=Y | | 4x-10x=14 |